Evaluation of Prescribing Pattern and Rational Use of Antibiotics at Surgery Department in a Tertiary Care Teaching Hospital - Raasi, K. Monika (International Journal of Pharmaceutical & Biological Archive, 2021)
Antibiotics are medicines that fight bacterial infections in people and animals. They work by killing the bacteria or by making it hard for the bacteria to grow and multiply. An antibiotic is a type of antimicrobial substance active against bacteria and is the most important type of antibacterial agent for fighting bacterial infections. These medications were widely used in the treatment and prevention of infections. Hence, there should be combined effort from all the health-care professionals and pharmacist to diversify the prescribing pattern of antibiotics, ideally by formulating prescribing guidelines, to make the prognosis and therapy more effective and for the ultimate goal of welfare of patient. This study concluded that, the ANTIBIOTIC use was found to be reasonable and rational in all the cases, all the antibiotics were prescribed from inside the essential drug list.